Evaluation of maize plant fractions submitted to different levels of nitrogen fertilization - Santos, Leandra Cristina Soares; Madureira, Mariana Rabelo; Júnior, Carlos Antônio Dias; Matos, Victoria Leite de; Neto, Otaviano Pires; Moura, Marielly Maria Almeida; Pires, Daniel Ananias de Assis; Costa, Renê Ferreira; Oliveira, Rogério Santos; Santos, Brisa Lafetá Rabelo; Nascimento, Leonardo Batista do; Versiani, Ana Ariela Gusmão (Seven Editora, 2024)
The use of nitrogen fertilizers in the appropriate dosage can modify the bromatological compositions of the plant. The objective of this study was to evaluate the chemical composition of the fractions of the corn plant submitted to different levels of fertilization. The experiment was carried out in the municipality of Bocaiúva, located in the interior of Minas Gerais. In the execution of the experiment, the transgenic corn VT PRO 3 from Agroceres was used. The experiment was arranged in a randomized block design with five replications. The treatments consisted of four N doses: 100, 200, 300 and 400 kg N/ha/cut). A single source of N, urea, was used. The data obtained were submitted to analysis of variance and regression analysis. The increase in nitrogen doses influenced the crude protein content of the corn plant. The maximum point for CP content was observed at a dose of 173 N (Kg/ha), and 20.01% of CP was observed. The neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of the stem were influenced by the increase of N rates (p < 0.05). It is concluded that in the results obtained there was an influence of nitrogen fertilization on the chemical composition of corn. DOI:https://doi.org/10.56238/sevened2024.007-073